2006
DOI: 10.1093/alcalc/agl007
|View full text |Cite
|
Sign up to set email alerts
|

Combined Acamprosate and Naltrexone, With Cognitive Behavioural Therapy Is Superior to Either Medication Alone for Alcohol Abstinence: A Single Centres' Experience With Pharmacotherapy

Abstract: The addition of both medications (naltrexone and acamprosate) resulted in measurable benefit and was well tolerated. In this patient population naltrexone with CBT is as effective as combined medication with CBT, but the trend favours combination medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 18 publications
1
38
0
2
Order By: Relevance
“…Concerning the combined treatment with both compounds, 3 trials have been published so far. Two of them (Feeney et al, 2006;Kiefer et al, 2003) found an additive effect if both drugs were combined, indicating that there might be a synergistic effect. Alternatively, a differential effect could be assumed.…”
Section: A Prospective Approach To Predict Response To Acamprosatementioning
confidence: 99%
“…Concerning the combined treatment with both compounds, 3 trials have been published so far. Two of them (Feeney et al, 2006;Kiefer et al, 2003) found an additive effect if both drugs were combined, indicating that there might be a synergistic effect. Alternatively, a differential effect could be assumed.…”
Section: A Prospective Approach To Predict Response To Acamprosatementioning
confidence: 99%
“…3. There is good evidence supporting adjunctive pharmacotherapy for alcohol, nicotine, and heroin dependence (Feeney, Connor, Young, Tucker, & McPherson, 2006;Hettema & Hendricks, 2010;Ling, Hillhouse, Ang, Jenkins, & Fahey, 2013). 4.…”
Section: Assessmentmentioning
confidence: 99%
“…Another large study (over 580 subjects, treated for 6 months) in the United Kingdom failed to find a difference between the treatment effects of acamprosate and placebo [101], but intervention commenced 25 days after recovery from physical withdrawal symptoms, a substantially large latency compared to the other studies [19]. A meta-analysis of these studies and others [18,102105] concluded a significant benefit for acamprosate treatment as assessed 6 months after the start of treatment [106]. A more recent analysis of the clinical data, where the effect of treatment in male and female subjects were analyzed separately, confirmed this conclusion and reported no sex differences in the beneficial effects of acamprosate [107].…”
Section: Clinical Developmentmentioning
confidence: 99%